Christina Rossetti : Faith, Gender and Time - D'Amico, Diane, 1951- (Book collections on Project MUSE., 1999)
"Since Arthur Symons's declaration in 1895 in the Saturday Review that Christina Rossetti was "among the great poets of the nineteenth century," Rossetti's image among critics has undergone permutations as divergent as Victorian culture is from postmodern. Now Diane D'Amico redeems Rossetti from the various one-dimensional castings assigned her across the generations - those of a saint writing poetry for God; of a sexually repressed, neurotic woman of minor talent; and, most recently, of a subversive feminist questioning the patriarchy - and renders a fuller, more intricate understanding of the poet than any to date. With logic, balance, and clarity, D'Amico seals her case that Rossetti's faith, her gender, and the times in which she lived should all be considered to appreciate her poetic voice."--Jacket.